2013
DOI: 10.1186/2046-0481-66-21
|View full text |Cite
|
Sign up to set email alerts
|

Herd health status and management practices on 16 Irish suckler beef farms

Abstract: BackgroundThere have been few studies published internationally which document herd health management practices in suckler beef herds and no published Irish studies. The study objective was to document herd health status and management practices on sixteen Irish suckler beef herds over a two year period (2009–2010). The farms used in the study were part of the Teagasc BETTER farm beef programme. The mean (s.d.) herd size, stocking rate and farm size was 68 cows (27.6), 2.0 LU/ha (0.3) and 64.3 (21.6) adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In a previous study on these farms [ 1 ], we reported that, on average, 70 cattle were purchased per farm over a two year period (2009–2010). This was a high level of purchasing given that the mean herd size in 2010 was 68 cows.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a previous study on these farms [ 1 ], we reported that, on average, 70 cattle were purchased per farm over a two year period (2009–2010). This was a high level of purchasing given that the mean herd size in 2010 was 68 cows.…”
Section: Discussionmentioning
confidence: 99%
“…A key component of profitable suckler beef production is calf output. In Ireland, a target of 0.95 calves weaned per female mated is the desired production goal [ 1 ]. Thus, any factors affecting calf output either directly through increased calf mortality, reduced calf performance or indirectly through reduced herd reproductive performance will affect both farm profitability and sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire addressed herd health management issues and major health problems observed during 2020 by farmers, as a modified version of the questionnaire used in a previous study [ 30 ]. Our questionnaire was completed by a preliminary assessment of management practices occurring in Azorean farms.…”
Section: Methodsmentioning
confidence: 99%